(untitled) (Heritage, 2022)
Adaptive behaviour is defined as a set of conceptual, social and practical skills that are learned and used in everyday life. Assessment of adaptive behaviour is an indispensable part in the identification and classification of intellectual disabilities, but also an important indicator of the development of children with other developmental disorders and children of typical development. The sample was divided into three groups: children with specific language impairment (SLI), children with mild intellectual disability (MID) and children with typical development (TD). The Adaptive Behaviour Diagnostic Scale (ABDS; Pearson - Patton - Mruzek 2016) was used to assess adaptive skills. The objectives of the study were to compare the levels of mastery of adaptive skills in children with SLI, MID and TD children, as well as to examine the impact of each of the individual domains (conceptual, social and practical) on the overall score of adaptive behaviour. The research results showed that children with SLI and MID have significantly poorer achievements compared to TD children. However, although children with SLI have poor performance, the results showed that adaptive skills of these children are significantly better compared to children with MID. Regresion analysis showed that conceptual skills are the best predictor of adaptive behaviour in TD children, while social skills are the best predictor of adaptive behaviour in both children with SLI and children with MID.